Reduction of computation time of Seismic Migration using FPGAs and GPGPUs: A review article. (2013)
This article makes a review around the eﬀorts that are currently being carried out in order to reduce the computation time of the MS. We introduce the methods used to make the migration process as well as the two computer architectures that are oﬀering better processing times. We review the most representative implementations of this process on these two technologies and summarize the contributions of each of these investigations. The article ends with our analisys about the direction that future research should take in this area.